ANALYSIS OF FACTORS THAT INFLUENCE COMMUNITY PARTICIPATION IN WASTE MANAGEMENT IN TOBELO SUB-DISTRICT, NORTH HALMAHERA DISTRICT - Sifrit Balida, Mario
Based on data from the Environmental Agency (2021), Tobelo Sub-district is the largest contributor to waste in North Halmahera Regency because the economic center and population growth are centered in this sub-district which makes waste problems one of the main problems in the future. To deal with waste problems, special handling is needed, one of which is communitybased waste management. In this research, the level of community participation in managing waste in Tobelo sub-district is measured and the factors that influence it are viewed from two factors, namely internal factors and external factors. The internal factors are age, education, occupation, income, knowledge, and attitude with the largest relationship strength being the attitude indicator, which is 29% of the 350 respondents. By using chi square test analysis, Kendall's tau-b test obtained indicators that are significantly related to community participation are the level of education, attitude, facilities, and the role of government. While cluster analysis and determination analysis obtained the results that a person whose attitude, facilities and government role are lacking, then that person can be grouped as a community that plays a less role in waste management with a degree of accuracy of 67.4%. Data were collected through questionnaires which were then analyzed using IBM SPSS software through the crosstabs and classify features.